1990
DOI: 10.1152/ajpcell.1990.259.5.c746
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte cation permeability induced by mechanical stress: a model for sickle cell cation loss

Abstract: Human red blood cells were subjected to mechanical shearing in a Couette viscometer at 37 degrees C, using polyvinylpyrrolidone to increase the medium viscosity. At stresses greater than 300 dyn/cm2, movement of both Na and K down their concentration gradients was observed. The net rate of both monovalent cation fluxes appeared to be linear with applied stress in the range of 300-910 dyn/cm2. The applied shear forces caused no fragmentation of the cells. Observed hemolysis was slight. The observed cation fluxe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 26 publications
2
16
1
Order By: Relevance
“…Previous studies, performed under somewhat different conditions, suggested that application of shear stress can cause leakiness to calcium (13). The leak pathway we have studied is not calcium dependent (6,9), indicating that if calcium does gain entry during deformation it does not reach levels able to stimulate calcium-activated K channels. Whether calcium in lesser amounts is entering RBC during our studies is not determined yet.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Previous studies, performed under somewhat different conditions, suggested that application of shear stress can cause leakiness to calcium (13). The leak pathway we have studied is not calcium dependent (6,9), indicating that if calcium does gain entry during deformation it does not reach levels able to stimulate calcium-activated K channels. Whether calcium in lesser amounts is entering RBC during our studies is not determined yet.…”
Section: Discussioncontrasting
confidence: 45%
“…It is fully reversible so that cells return to their normal state upon cessation of deformation (6). The leak is balanced so that induced Na influx equals K efflux, it is lower at low pH, and it is not chloride dependent (6,9). Previous studies, performed under somewhat different conditions, suggested that application of shear stress can cause leakiness to calcium (13).…”
Section: Discussionmentioning
confidence: 99%
“…Third, the survival of an LPC-treated RBC subpopulation might be because of their S/V ratio returning toward normal values through a decrease in cell volume as a result of regulation of ions and water permeability of the cell. [2][3][4][5] It is well established that, when submitted to increased mechanical stress, normal RBCs exhibit a reversible increase in permeability to monovalent [2][3][4][5]32,33 and divalent 5,34 cations and to anions. 5 Such phenomena have been shown to be exacerbated when RBC membrane rigidity is increased 3 or when the surface area is reduced, as is the case in HS RBCs.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological shear stress in the circulation has been claimed to cause a reversible increase in Ca 2+ permeability[6], [7], [8], [9], [10]. Recent evidence supported the view that the increasing density of aging human RBCs, attributed to a progressive loss of KCl and osmotic water, results from the cumulative effects of declining Ca 2+ extrusion capacity of the plasma membrane Ca 2+ pump, aided by minor episodes of increased Ca 2+ permeability in the circulation [11], [12], [13], [14], [15].…”
Section: Introductionmentioning
confidence: 99%